THE CORRELATION BETWEEN STUDENTS’ METACOGNITIVE READING STRATEGY AND READING COMPREHENSION AT THE SECOND YEAR OF SMA SERIRAMA YLPI PEKANBARU - Kandau, Cindy Nisa Aruni; Hasan, Samsi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This research was conducted because some problems were faced by students in reading, especially in metacognitive reading strategy and reading comprehension. The problems were: most of the students are lazy to read the text, most of them feel bored when studied English especially in reading the text, most of them still have less metacognitive strategy in reading text, and most of them have low ability in reading comprehension. The objective of this research was to investigate the correlation between metacognitive reading strategy and reading comprehension at second year of SMA Serirama YLPI. This research was a quantitative research. The population of this research was all of the students at second year. The total number of population was 30 students.Total sampling is the best way to obtain a representative sample.The instruments were questionnaire and test. Person product moment correlation coefficient was used to analyze the data. The result so this research showed that the coefficient correlation was0.109 and the p-value was (0.565) which was greater than 0.05 (0.565 > 0.05). It means that Ho is accepted and Ha is rejected. Based on the result of the research it could be concluded that there was no statistically significant correlation between students’ metacognitive reading strategy and reading comprehension at second year of SMA Serirama YLPI Pekanbaru.